1999
DOI: 10.1177/021849239900700102
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia after Cardiopulmonary Bypass: A Prospective Study

Abstract: Postoperative hyperbilirubinemia is one of the complications of cardiopulmonary bypass. This prospective study was conducted on 77 patients who underwent open-heart surgery, to evaluate the incidence, risk factors, and prognostic significance of postoperative hyperbilirubinemia. Liver function tests were conducted preoperatively, immediately after surgery and on the 1st, 3rd, and 7th postoperative days. The overall incidence of postoperative hyperbilirubinemia was 26%. The incidence was significantly higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…13–15 Chandra and colleagues reported an overall incidence of hepatic dysfunction to be as high as 26%, but, on excluding patients with preoperative hyperbilirubinemia, the actual incidence was found to be 19%. 16 Similarly, in a patient group undergoing cardiac surgery with normal preoperative liver function tests, Mastoraki et al reported postoperative hyperbilirubinemia to be 26.5%. 17…”
Section: Discussionmentioning
confidence: 95%
“…13–15 Chandra and colleagues reported an overall incidence of hepatic dysfunction to be as high as 26%, but, on excluding patients with preoperative hyperbilirubinemia, the actual incidence was found to be 19%. 16 Similarly, in a patient group undergoing cardiac surgery with normal preoperative liver function tests, Mastoraki et al reported postoperative hyperbilirubinemia to be 26.5%. 17…”
Section: Discussionmentioning
confidence: 95%
“…These underwent full-text review. Finally, 10 studies with 6,100 subjects were included in the present systematic review (3,(7)(8)(9)(10)(12)(13)(14)(15)18). The characteristics of the included studies are summarized in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…All of the included studies were observational in design. Seven (70%) of the included studies enrolled prospective cohorts (3,(8)(9)(10)(13)(14)(15)18). Of these included studies, the criterion for hyperbilirubinemia diagnosis was lower than 3 mg/dL in 4 studies and higher than 3 mg/dL in 6 studies.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously proved that the use of CPB is related to early hyperbilirubinemia and transient liver dysfunction [ 14 , 18 ]. Nonetheless, the mortality rates of patients with severe hyperbilirubinemia were heterogeneous in previous reports.…”
Section: Discussionmentioning
confidence: 99%